Agriculture-Related Businesses' Financial Health Amid The COVID-19 Pandemic - Roman BLAZEK; Pavol DURANA (Communications of International Proceedings, 2022)
Financial stability is one of the company's top priorities. When the Covid-19 pandemic broke out, many businesses were forced to make the decision between cutting back on production, raising the price of their goods, or terminating their staff. The most at risk industry was agriculture because it depends so heavily on grants and subsidies. The gradual rise in the cost of manufactured items also affected consumer demand for diverse agricultural products' ultimate products. Each of these conditions prompted the creation of the current study, which looks at how well-equipped Slovak and Czech companies were to adjust to the economic changes brought on by the epidemic. The CH-index, which is specifically targeted at businesses active in agriculture, forestry, and fishing, was utilized to examine the provided firms. The data from the Orbis database was recalculated in Microsoft Excel to create the model that was provided. The article's conclusion is that the coronavirus pandemic, which severely affected all industries, did not cause the situation at the agriculture sector-focused businesses under observation to get worse. It's possible that the manufactured commodities just meet fundamental demands rather than greater ones.
Keywords: Financial health. Ch-Index. Orbis database. Slovak republic. Czech Republic.